Redes Neurais Atratoras em Topologias Complexas - Galhardo, Carlos Eduardo Cardoso (2006)
In this work we present some modifications in the Hopfield model for attractor neural networks. First, in order to bring the model closer to a biological network of neurons, we introduce a controlled dilution generating complex topologies. This modification is supported by experimental evidences [1, 2]. Then, study the relation between eficiency and the topologies, in the recovery stored patterns. We study how the network topology play a role in the model, by introducing correlated patterns and studing the performance of each topology as the correlation between patterns is increased.